2015
DOI: 10.13110/humanbiology.87.2.0092
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Otitis Media: A Review, and a Model to Explain High Prevalence in Indigenous Populations

Abstract: Inflammation of the middle ear (otitis media) comprises a group of disorders that are highly prevalent in childhood, and indeed are amongst the most common disorders of childhood. Otitis media is also heritable, and has effects on fecundity. This means that otitis media is subject to evolution, yet the evolutionary selection forces that may determine susceptibility to otitis media have never been adequately explored.Here I undertake a critical analysis of evolutionary forces that may determine susceptibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 173 publications
0
18
0
Order By: Relevance
“…26 Indigenous populations may be at greater risk of developing otitis media because of factors related to colonisation, including exposure to high population density pathogens since colonisation, and the influence of socioeconomic conditions (which drive infection), particularly in remote areas. 27 In other indigenous populations, there has been a trend towards decreased otitis media. Amongst Arctic Circle Inuit school children, otitis media prevalence decreased from 30-50 per cent in the 1960s to around 10 per cent in the 1990s.…”
Section: Epidemiologymentioning
confidence: 99%
“…26 Indigenous populations may be at greater risk of developing otitis media because of factors related to colonisation, including exposure to high population density pathogens since colonisation, and the influence of socioeconomic conditions (which drive infection), particularly in remote areas. 27 In other indigenous populations, there has been a trend towards decreased otitis media. Amongst Arctic Circle Inuit school children, otitis media prevalence decreased from 30-50 per cent in the 1960s to around 10 per cent in the 1990s.…”
Section: Epidemiologymentioning
confidence: 99%
“…While 10 to 20% of nonindigenous children develop chronic or recurrent OM, the condition is almost universal among Australian Aboriginal children by 12 months of age and persists to school age (4ā€“6). OM is also endemic in other indigenous populations, such as Native American, Greenlandic and Alaskan Inuit, and Maori populations (7); however, the rates of OM reported for Australian Aboriginal children are the highest in the world (8). …”
Section: Introductionmentioning
confidence: 99%
“…The genetic contribution to OM susceptibility became evident in the 1980s after several studies showed that the prevalence of OM was disproportionately high in some ethnicities (native Americans and Australian aborigines) and relatively low in individuals of African ancestry (Clements, 1968;Bhutta, 2015). A surveillance study on ear and nasopharyngeal carriage was conducted among remote Australian aboriginal communities in 2013 and found that 50% of young children (mean age 13 months) had OME, 37% had AOM, and 12% had CSOM (Leach et al, 2016).…”
Section: Early Studiesmentioning
confidence: 99%